Patched removal of the mantle lithosphere under orogens: A systematic numerical study - Lei, Tian; Liao, Jie; Li, Zhong-Hai; Liu, Mian; Li, Lun (Frontiers in Earth Science, 2023)
Delamination or convective thinning could cause large-scale and complete removal of mantle lithosphere under orogens. However, geological and geophysical observations suggest that patched removal of mantle lithosphere has occurred in some orogens, such as the northeastern Tibetan plateau, the central Tianshan, and the central Andes. Dislocation-creep-induced strain localization cannot promote effective removal of mantle lithosphere to Moho in small-scale. Recent rheological studies proposed that the dislocation-accommodated grain boundary sliding (DisGBS) may dominate the upper mantle deformation. DisGBS could make the lower lithospheric mantle rheologically weaker than dry olivine. With 2-D high-resolution thermo-mechanical modeling, we systematically investigated the conditions for the initiation of small-scale lithospheric thinning under orogens and explored the minimum range of removing mantle lithosphere. The numerical results indicate that classical convective drip cannot effectively thin the mantle lithosphere to Moho in small-scale range. In contrast, small-scale thinning can be induced by lithospheric heterogeneity with DisGBS and plasticity. The rheological heterogeneity can be verified by magmatism and metasomatism under central Andes and orogens between terranes under northeastern Tibetan plateau or Tianshan.